Analisis Pengaruh Indikator Ekonomi Dan Kinerja Perbankan Syariah Terhadap Penyerapan Tenaga Kerja Pada Perbankan Syariah Di Indonesia Tahun 2008-2014 - Kurnia Sari Kasmiarno; Karjadi Mintaroem (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aims to find out the relationship both simultaneosuly and partially of the eefect of PDB Real Bank, Syariah Banking Investment and the total of syariah banking financing towards the amount of employees in syariah banking. The approach used in this research is quantitative approach that uses multiple regression with Ordinary Least Square (OLS) method which has four variables that are PDB real bank, syariah banking investment and syariah banking financing as independent variables, meanwhile the amount of employees in syariah banking acts as a dependent variable. The result shows that all of the independent variables have positive/significant relationship towards the amount of employees in syariah banking in Indonesia between 2008-2014. . This shows that all of independent variables are able to explain the dependent variable accurately since the coefficient value obtained was high.